Educational Innovation of Islamic Boarding Schools in Indonesia and Malaysia in Facing the 21st Century Challenges - Asror, Moh; Mahfudloh, Ririn Inayatul; Kusaeri, Kusaeri; Rusydiyah, Evi Fatimatur (Universitas Muhammadiyah Magelang, 2023)
The problem of 21st Century education is in facing the challenges to produce generations with ability to think critically and skills in solving life problems. The challenges can be responded through educational innovation in Islamic boarding schools. The purpose of the research is to analyze the forms of educational innovation made by Islamic boarding schools in Indonesia and Malaysia in facing the 21st Century. This research uses systematic literature review (SLR) type of qualitative approach. The tools used to codify the literatures are Publish and Perish, ERIC, and Google Scholar. The codification result finds 64 articles on Islamic boarding schools innovation in Malaysia and 207 articles on it in Indonesia. The articles codified are limited from 2013 -2023. The result of the research shows that there are differences between educational innovations in Indonesia and Malaysia in the period of 2013 to 2023 in the aspects of the use of technology, community involvement, collaboration with other educational institutions, combination of religious and general education, and in the aspect of project-base education. The similarities between the two are in increasing the faith of Muslims through religious education and creating generations of noble character. To face the challenges of the 21st century requires the role of a transformational and distributive leader who can form unity, partnership, cooperation, democracy, tolerance, and involvement in leadership practices.